2007
DOI: 10.1007/s10152-007-0093-4
|View full text |Cite
|
Sign up to set email alerts
|

Trophic and environmental drivers of the Sechura Bay Ecosystem (Peru) over an ENSO cycle

Abstract: Interannual environmental variability in Peru is dominated by the El Niño Southern Oscillation (ENSO). The most dramatic changes are associated with the warm El Niño (EN) phase (opposite the cold La Niña phase), which disrupts the normal coastal upwelling and affects the dynamics of many coastal marine and terrestrial resources. This study presents a trophic model for Sechura Bay, located at the northern extension of the Peruvian upwelling system, where ENSO-induced environmental variability is most extreme. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Several studies have suggested that the continuous gametogenic activity in A. purpuratus is a strategy of adaptation to the combination of environmental conditions, especially temperature and food availability (Illanes et al 1985, Wolff 1988, Avendaño et al 2008. A small seasonal increase in river inflow seems to disturb the gametogenic activity of A. purpuratus as seen in Paita (Taylor et al 2008). Low temperatures at the southern limit of the distributional range may limit the gametogenic activity to a shorter season.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the continuous gametogenic activity in A. purpuratus is a strategy of adaptation to the combination of environmental conditions, especially temperature and food availability (Illanes et al 1985, Wolff 1988, Avendaño et al 2008. A small seasonal increase in river inflow seems to disturb the gametogenic activity of A. purpuratus as seen in Paita (Taylor et al 2008). Low temperatures at the southern limit of the distributional range may limit the gametogenic activity to a shorter season.…”
Section: Discussionmentioning
confidence: 99%
“…Since the intensity and onset of EN and thus its impact on PaciWc South America strongly varies (Arntz and Fahrbach 1991), management advice tailored to small-scale users is necessary (i.e. Taylor et al 2008;Thatje et al 2008) to evaluate the variable responses of coastal ecosystems along PaciWc South America to climate oscillation, particularly as they have much less destructive track records of resource use than industrial-scale operations, at least unless they are forced into direct competition. …”
Section: S Thatje (And)mentioning
confidence: 99%
“…However, when trying to reveal the development and resilience potential of coastal marine communities, the lack or inaccessibility of information is a general concern Riascos et al 2008). Most studies on the biology and ecology of organisms occurring in upwelling regions are of descriptive nature and underlying processes that are driven by ENSO are far from being understood (Criales-Hernández et al 2008;Sotil et al 2008), which hampers the development of (short-term) predictive or response-management of key resources (Taylor et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The diet matrix of the reference model was modified in light of the fact that many groups are rather unselective, opportunistic feeders and that available food item proportions had changed due to the El Niño-caused changes in biomass of most groups. Following the method of Taylor et al (2008a), we thus adjusted the diet proportions to reflect predatory groups' consumption habits as well as the available production of prey groups. Moreover, an increased base percentage of detritus feeding (10%) was assumed for most benthic feeders, which is proximate to values given in Ortiz & Wolff (2002) and Taylor et al (2008b) for benthic compartments in a Chilean and Peruvian bay system, respectively.…”
Section: Comparing the Reference Model And The El Niño State Model Ofmentioning
confidence: 99%